PERENCANAAN PERSEVASI JALAN KONDISI RUAS JALAN DI KOTA PALEMBANG MENGGUNAKAN ASPAL CPHMA - Sari Dewi, Anggi Purnama; Prasetyo, Teddy (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2024)
Maintenance of road and bridge infrastructure has a crucial role in maintaining transportation efficiency and encouraging economic growth in urban areas. In the city of Palembang, which is one of the major cities in Indonesia, good road and bridge conditions are needed to support people's economic and social activities. Population growth and high intensity of use make the need for routine maintenance even more urgent. Cold Paving Hot Mix Asphalt (CPHMA) technology emerges as an effective solution by offering ease of application, high resistance to traffic loads, and long-term maintenance cost efficiency. Maintenance planning that takes into account factors such as traffic intensity, geographical conditions, and budget constraints is essential to ensure the infrastructure remains in optimal condition. With proper planning and the use of appropriate technology, the condition of roads and bridges in Palembang is expected to continue to be maintained, reduce the risk of accidents, attract investment, and improve the image of the city.